Kepuasan Kerja Karyawan Bagian Fresh Food pada Tiara Dewata Supermarket - UTOMO, RM SATRIO GUMULYA; ANTARA, MADE; SURYAWARDANI, IGA OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.3, Juli 2019, 2019)
Employee’s Job Satisfaction at Fresh Food Department Tiara Dewata Supermarket Efforts to obtain optimal performance from the presence of employees in a company need to be done by setting the right strategy, namely by thinking about how to manage employees so that they are able to achieve the company's objectives. This can be realized by creating job satisfaction of the members of the organization concerned which will further improve work performance. The objectives of this research are: (a) To analyze job satisfaction at Tiara Dewata Supermarket. (b) To analyze the factors forming employee job satisfaction at Tiara Dewata Supermarket. The population in this study were all employees of Tiara Dewata Supermarket in the fresh food department with total 60 people. The sample was determined by Saturated Sampling method, which is a sample determination technique if all members of the population were used as samples. Data analysis method used is factor analysis, namely The First Order Confirmatory Factor Analysis and The Second Order Confirmatory Factor Analysis, which is processed using AMOS 22 software. The results show that: (1) Fresh Food employees at Tiara Dewata Supermarket are very satisfied working under the auspices of the Tiara Dewata Supermarket, this can be seen from the results of the average assessment score consisting of: main tasks and work functions, supervision by the leadership, opportunities for advancement, co-workers, and working conditions, with an average overall score of 4.40 at an interval of 4.2-5.0. (2) All research factors and indicators are valid / significant as a measure or form of employee job satisfaction. Overall the factors that give the biggest contribution or the strongest measure of job satisfaction is the opportunity to progress with the value of loading factor 0.986, while the factors that give the smallest contribution or the weakest as a measure of the construct of job satisfaction are co-workers with the value of loading factor 0.943.